Trade facilitation small economies and the WTO negotiations - Williams, Peter (Commonwealth Secretariat LondonGB, 2003)
Identifies the interests of the Members of the CARICOM, the Indian Ocean Commission and the Pacific Islands Forum. Examines how best they might defend these interests, nationally, regionally and in the negotiating group.